Trek Kaleci Penggunaan Media Trek Kaleci Untuk Meningkatkan Kemampuan Konsep Berhitung Siswa - Nirwan Hadiansyah; Rostina Sundayana (Jurnal Padegogik, 2023)
The background of this research is the results of the repetition of mathematics lessons in class III students at SDN 4 Cigedug at the end of semester 1 of the 2021/2022 academic year. Only 55% of grade III students whose grades exceed the KKM. The lack of ability to understand the concept of multiplication and division in students is one of the factors in obtaining these scores. The use of instructional media is expected to be able to improve students' ability to understand mathematical concepts, one of which is the kaleci track. Trek kaleci is a mix between Trek (racing track) and kaleci (marbles). Trek Kaleci is also an acronym for Math Practice using Kaleci. The purpose of this study was to analyze the improvement of students' numeracy concept skills through the use of the Kalali Track learning media on multiplication and division of simple numbers. This study uses a qualitative method, with research instruments in the form of essay tests and interviews with an orientation towards improving students' numeracy concept abilities and the use of Trek Kaleci media. Grade III students at SDN 4 Cigedug are the sample used in this study. Based on the results of the analysis, the average value of students' numeracy concept ability was 9.2 out of 12, with a percentage of 76%. Then based on the results of the questionnaire analysis interviewing students, a positive response was received with a percentage of 91% of students enjoying learning mathematics using Trek Kaleci.